Effect of Physical Work Environment, Workload and Tenure on Teacher Performance at High School - Mulyadi, Sasra; Aryadi, Didi (Management of Education: Jurnal Manajemen Pendidikan Islam, 2025)
This study aims to analyze the effect of physical work environment, workload, and tenure on teacher performance at SMA Negeri 1 Basa Ampek Balai, Pesisir Selatan Regency. Specifically, this study evaluates: (1) the effect of physical work environment on teacher performance; (2) the effect of workload on teacher performance; (3) the effect of tenure on teacher performance; and (4) the simultaneous effect of physical work environment, workload, and tenure on teacher performance. This study used a quantitative approach with a total sampling technique, in which the entire population of 50 teachers was sampled. The results of the analysis showed that: (1) the physical work environment has a positive and significant effect on teacher performance; (2) workload has a negative and significant effect on teacher performance; (3) tenure has a positive and significant effect on teacher performance; and (4) simultaneously, the physical work environment, workload, and tenure have a positive and significant effect on teacher performance at SMA Negeri 1 Basa Ampek Balai. These findings confirm the importance of creating a conducive work environment, managing workload proportionally, and recognizing tenure in efforts to improve teacher performance.